DEVELOPMENT OF HYGIENIC PROPERTIES EMBEDDED INDIVIDUAL MEANS WITH PLANT INSERTS IN FOOTWEAR - LESHCHYSHYN, MARYNA; IUNGIN, OLGA (Technologies and Engineering, 2022)
Purpose: To conduct experimental studies of embedded hygienic installed insoles with tableted plant inserts in footwear Methodology. The properties of embedded hygienic insoles have been studied for vapor permeability and moisture content according to the methods of GOST 22900-78. The solid inserts were ground and extracted with distilled water for a week to obtain aqueous extracts for microbiological studies. Determination of antimicrobial activity was performed using a culture of S.aureus ATCC 25923 in microtiter 96-well plates in liquid nutrient medium NB spectrophotometrically by optical density (Hipo MPP-96, Biosan, λ = 620 nm, control medium – by the location of a non-sterile sample with (30 × 30 mm) on the surface of sterile NA medium. Findings. To improve the hygienic characteristics of the inner space of the shoe, the research presents embedded hygienic products with solid inserts in the form of tablets from the plant raw materials of medicinal thyme and sage. The technological characteristics of tableted inserts from vegetable raw materials are given. The results of vapor permeability and moisture content in the studied samples are obtained, which correspond to the normative values according to GOST 940-81 and are safe for human feet. Originality. Determination of indicators of vapor permeability and moisture content of embedded hygienic installed insoles with tableted plant inserts and establishing their compliance with regulatory requirements. Determined the regularities of inhibitory effect of aqueous extracts of thyme on the growth of biomass of gram-negative bacteria in planktonic culture. Practical value. Another advantage of custom-made shoes is the ability to consider the customer's preferences regarding shoe care products during the operation. At the same time, an important task is to ensure the hygiene of the inner space of the shoe through the use of insoles containing elements obtained from medicinal plant materials.